Challenges of implementing restorative justice for intimate partner violence: An Islamic perspective. Issue 3 (3rd July 2018) - Islam, Md. Jahirul; Suzuki, Masahiro; Mazumder, Nurunnahar; Ibrahim, Nada
ABSTRACT: Intimate partner violence (IPV) is currently recognized as a critical public health concern and a human rights issue. Not surprisingly, Muslims – a religiously and socio-culturally diverse faith-based populace – are not an exception. To address this complex area of criminal justice and social policy, some scholars advocate implementing restorative justice (RJ) approaches. While RJ approaches have been traditionally used in Islamic cultures for conflict resolutions, to date, few studies have investigated how RJ operates in dealing with IPV in Muslim countries and communities. This article explores how RJ approaches towards IPV operate in some Muslim countries/communities, and offers insights into developing culturally and religiously appropriate ways of implementing RJ in IPV situations among Muslims. Given the prevalence of IPV among Muslims, the question is particularly important and timely. Taking exclusively limited examples of RJ approaches that have been used to mediate IPV cases in Muslim countries and communities, this paper found one significant challenge in the RJ approaches among Muslims: community acceptance of IPV. To reduce IPV in Muslim society, it is necessary to develop treatment models and techniques that meet cultural and religious needs. This paper found that since RJ is not alien to Islamic teachings, RJ approaches can be implemented effectively in dealing with IPV among Muslims by ensuring justice and equity of the abused woman. The findings of this paper will assist policymakers, practitioners, and service providers in providing religiously and culturally appropriate care when addressing IPV issues among Muslims.